Green synthesis of iron-oxide nanoparticles using scrap iron as precursor for the removal of Pb (II) from aqueous medium - Taqui, Mohd; Das, Sneha; Kamilya, Tuhin; Mondal, Sandip; Chaudhuri, Surabhi (Journal of Environmental Engineering and Landscape Management, 2022)
In the present study, low-cost, environmentally friendly, single-step, high productive novel Iron-oxide nanoparticles (NPs) were prepared from scrap iron using a green synthesis method to remove Pb (II) from aqueous solution. The characterization of synthesized nanoparticles was conducted by UV-vis spectroscopy. The crystalline structure and the phase change were clarified by XRD. FE-SEM was done to know the morphology of iron oxide nanoparticles, and the average surface area of 46.856 m2/g was found by the BET surface area analyzer. The XRD plot shows that the obtained magnetite Fe3O4 combines FeO and Fe2O3 as the synthesis was conducted in the open atmosphere. The SEM images confirm the formation of iron oxide nanoparticles with a size of 31 nm. The removal efficiency of the adsorbent was carried out by optimizing the different operational parameters like pH, time, adsorbent dosage, initial concentration of metal ion, contact time by batch studies. The obtained pHzpc (pH 5.7) value indicates that the adsorption process will be favorable at higher pH. The maximum removal efficiency and uptake capacity of lead were 98% and 68.07 mg/g, respectively. Adsorption data obtained were analyzed with Langmuir and Freundlich isotherm equations. The equilibrium data are fitted by Langmuir isotherm in a superior way than that of Freundlich isotherm. The results show that homogeneous adsorption of the metal ion favors heterogeneous adsorption. The maximum adsorption capacity of iron oxide NPs was calculated through Langmuir isotherm was Qmax (68.07) mg/g. Moreover, the adsorption of metal ions with time was also analyzed with the pseudo 1st and pseudo 2nd kinetic equations. The kinetic data are fitted more in the pseudo 2nd order reaction. Adsorption capacity calculated through pseudo 2nd order equation was qe (51.81) mg/g. This literature verifies that NPs synthesized from scrap iron as precursors prove to be an attractive option for removing heavy metals.